OP IV – 1 Childhood type 1 diabetes; an environment wide association study (ewas) across england. (18th March 2018) - Sheehan, Annalisa; Hodgson, Susan; Fecht, Daniela; Sterrantino, Anna Freni
Abstract : Background/aim: Type 1 Diabetes (T1D) is an autoimmune disease with 4 00 000 people currently affected across the UK. T1D results from gene-environment interactions, with environmental factors likely triggering the disease process in genetically susceptible individuals. We aim to assess the influence of a wide range of environmental factors on childhood T1D incidence in England. Methods: We undertook an ecological EWAS at the Local Authority District level (LAD) using a national Hospital Episode Statistics (HES) based incident T1D dataset, containing 1300 cases per year. There are 354 LAD's in England with an average of 1 39 689 persons. We compiled LAD-level estimates for a range of environmental exposures including sunshine duration, air temperature, ultraviolet radiation (UV), radon, air and light pollution, nitrates in drinking water, metals in soil, pesticides and green space; as well as information on land cover type, urban/rural status, tobacco expenditure as a smoking proxy, population density, socioeconomic deprivation, and ethnicity. The associations between T1D incidence and these environmental variables were assessed via Negative Binomial regression. Results: The HES dataset included 13 948 eligible T1D cases aged 0–9 years old over the period April 2000 – March 2011. Case counts by LAD varied from 1 to 236; mean 39.4 (SD 25.7), with an overall incidence of 21.2 (95% CI: 20.9 to 21.6) per 1 00 000. Age and sex standardised incidence rates varied from 4.45 to 80.55 per 1 00 000. 22 out of 52 environmental exposures were significantly associated with diabetes incidence after adjusting for multiple testing using the Bonferroni correction (p values above the Bonferroni Corrected level of 0.0009). These included air pollutants PM10, PM2.5, NO2 and CO, light pollution, UV, population density and ethnicity. Conclusion: Our analysis contributes to evidence that a range of environmental exposures are associated with T1D in children in England. Variables identified as associated with T1D at the ecological level are being further assessed at the individual level in a case control study, using data from the After Diabetes Diagnosis Research Support System-2 (ADDRESS-2).